2014
DOI: 10.1161/strokeaha.114.006490
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Patient With Spinal Cord Infarction After a Hypotensive Episode

Abstract: A 72-year-old man with past medical history significant for peripheral vascular disease, bilateral carotid stenosis, hypertension, dyslipidemia, and heavy tobacco use developed sudden severe chest pain and received sublingual nitroglycerin with pain resolution. The patient was able to walk to the ambulance, but on arrival in the emergency room had a systolic blood pressure of 60 mm Hg, which was thought to be secondary to nitroglycerin. He was given intravenous fluids. A few hours later, he complained of being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 10 publications
(6 reference statements)
1
18
0
1
Order By: Relevance
“…The risks of transfusion must be balanced with the need to maintain appropriate levels of perfusion to end-organs and the spinal cord. There are several case reports describing infarctions of the portions of the spinal cord secondary to hypotension [5,7,8,49].…”
Section: Introductionmentioning
confidence: 99%
“…The risks of transfusion must be balanced with the need to maintain appropriate levels of perfusion to end-organs and the spinal cord. There are several case reports describing infarctions of the portions of the spinal cord secondary to hypotension [5,7,8,49].…”
Section: Introductionmentioning
confidence: 99%
“…Rao Shailaja et al 8 dalities. 3,6,7 The patient in this case was close to the transverse infarction.…”
mentioning
confidence: 65%
“…2 Patients typi cally present with acute back or neck pain at the onset of symptoms, and areflexic flaccid paraplegia or tetraplegia with loss of bowel and bladder continence. 3 The research reports a 34yearold woman developed spinal cord infarction after total hysterectomy, due to severe postpartum hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…Symptom onset was usually acute (minutes to hours) with some reporting TIA symptoms in the preceding years. No identifiable cause was found in 20 of the patients, but three had an episode of arterial hypotension preceding infarction and three had disk herniation [13]. CSF was shown to have increased protein but without pleocytosis or oligoclonal bands [13] (Table 2).…”
Section: Spinal Cord Infarctmentioning
confidence: 99%
“…The classic symptoms of SCI when the anterior spinal artery is involved are sudden ridiculer pain at the level involved, motor weakness, loss of sphincter control, spinothalamic deficits with sparing of dorsal column related vibration and Proprioception [12]. A retrospective review of 27 patients with confirmed spinal cord ischemia revealed that the majority of patients had anterior spinal artery syndrome with only a minority having transverse infarcts that caused a more severe central cord syndrome [13]. Symptom onset was usually acute (minutes to hours) with some reporting TIA symptoms in the preceding years.…”
Section: Spinal Cord Infarctmentioning
confidence: 99%